Qualidade de vida de pacientes após um ano do diagnóstico da COVID-19: estudo retrospectivo - Santos, Monyka Brito Lima dos (2023)
The aim was to assess the quality of life of patients one year after diagnosis of COVID-19. A descriptive, cross-sectional, retrospective, and quantitative study carried out in the Northeast of Brazil (Ceará, Pernambuco, and Maranhão), with a sample of 304 people who met the inclusion criteria: over 18 years old, diagnosed with COVID-19 from Jan/Dec/2021, notified in e-SUS Notifica or the Influenza Surveillance Information System (SIVEP-GRIPE). Data collection used the "Software for monitoring people with COVID-19 and other respiratory syndromes" assembled by a shared link. The software contained sociodemographic data, clinical and lifestyle information, and the Short-Form Health Survey (SF-36). McNemar's test verified the association between the variables. Student's t-tests and ANOVA compared the means. The study was approved by the Research Ethics Committee. One year after infection, the symptoms remained: anxiety, memory loss/difficulty concentrating, telogen effluvium, respiratory problems, anosmia, and ageusia, among other symptoms and sequelae. In the association of the SF-36 domains, anxiety was significant in the pain domain; memory loss in the physical limitation, general state of health, social aspects, and emotional limitation domains; telogen effluvium in the physical restriction, pain, general state of health, social factors, emotional limitation, and mental health domains; tiredness and fatigue in the functional capacity, limitation by physical aspects, pain, general state of health, restriction due to emotional aspects and mental health domains; respiratory problems in the functional capacity, pain and general state of health domains; hypertension in the vitality, social factors and limitation by emotional aspects domains. The highest QoL averages found in males were from patients aged > 60 years, Catholics, with primary education, married/stable union, income > 4 minimum wages, and living in the countryside. It's concluded that patients showed improvement in QoL after one year of infection by COVID-19, despite some symptoms and sequelae. Thus, it is necessary to design and implement health promotion and rehabilitation strategies focused on QoL and long term follow-up of people who have had COVID-19.